Biodiversity of Aspergillus section Flavi in Europe in relation to the management of aflatoxin risk - Perrone, Giancarlo; Gallo, Antonia; Logrieco, Antonio F. (Frontiers in Microbiology, 2014)
Aflatoxins and the producing fungi Aspergillus Section Flavi are widely known as the most serious and dangerous mycotoxin issue in agricultural products. In Europe, before the outbreak of aflatoxins on maize (2003-2004) due to new climatic conditions, their contamination was confined to imported foods. Little information is available on molecular biodiversity and population structure of Aspergillus Section Flavi in Europe. Preliminary reports evidenced the massive presence of A. flavus L-morphotype as the predominant species in maize field, no evidence of the highly toxigenic S-morphotype and of other aflatoxigenic species are reported. The risk of a shift in traditional occurrence areas for aflatoxins is expected in the world and in particular in South East of Europe due to the increasing average temperatures. Biological control of aflatoxin risk in the field by atoxigenic strains of A. flavus starts to be widely used in Africa and USA. Studies are necessary on the variation of aflatoxin production in populations of A. flavus to characterize stable atoxigenic A. flavus strains. The aim of present article is to give an overview on biodiversity and genetic variation of Aspergillus Sect. Flavi in Europe in relation to the management of aflatoxins risk in the field.